Teach yourself counselling - Milne, Aileen. 4 0 16; 5 (London : Teach Yourself, 2007)
A comprehensive guide to counseling skills and techniques, covering topics including stress management and cognitive behavioural therapy.
Includes bibliographical references and index.
Young Adult.
Keywords: 2 -- 0; 6; Counseling -- 20 -- Textbooks; 20; 2